Institutional Analysis of Drinking Water Supply System in East Nusa Tenggara Province - I Gede Eko Putra Sri Sentanu; Muhammad Edo Edi Sriyiono (Department of Public Administration, 2021)
The regulatory mandate states that the implementation of SPAM in the regions is prioritized for BUMD as the SPAM manager. If SPAM services are not reached by BUMD, then the implementation of SPAM remains the responsibility of the Central Government or Regional Governments may form a Technical Implementation Unit or Service Technical Implementation Unit to serve areas or areas that have not been reached by these services but can also be implemented by Community Groups and Business Entities to meet their own needs. The purpose of this paper is to analyze how the implementation of SPAM in NTT Province with the perspective of Good Corporate Governance. The research method used is literature review by utilizing relevant journals, books, media also laws and regulations. The results of this study indicate that the implementation of SPAM 2020 is mostly carried out by PDAM (15 districts/cities from 22 districts/cities in NTT), the remaining 7 districts are still in the form of UPTD BLUD and UPTD. Institutions are important to ensure that drinking water services to the community can be served properly, and ensure the functioning of SPAM, both funded by the APBN and APBD.